Empowerment of Micro, Small and Medium Enterprises Through Free Halal Certification Assistance to Strengthen Economic Independence Synergy in Triharjo Village - Reny Setiyowati; Rizka Febri Melindasari; Najata Hammada Jakti; Nahnu Robid Jiwandono (Universitas Kristen Indonesia Toraja, 2024)
Halal certification on business products is an aspect that is always considered by every consumer. Indonesia as a country with a majority Muslim population, always maintains that every product circulating in the community has been halal certified. However, in reality, there are still many products that have not been certified halal due to the lack of knowledge and information possessed by business actors. KKN MIT 18 Post 58 UIN Walisongo together with Walisongo Halal Center took proactive steps to provide socialization and assistance for MSME actors in Triharjo Village to obtain halal certification for their products. This program applies the Service-Learning method by showing the commitment and direct contribution of students in empowering sustainable solutions in the community. This program aims to expand the market reach of their products, encourage MSMEs to consistently provide quality halal products and enhance economic independence for the people of Triharjo Village in a sustainable manner.